Finitude, Necessity, and Healing from Despair in Kierkegaard's The Lily and the Bird - Strelis Söderquist, Anna Louise (Journal of religious ethics, 2024)
This study underscores The Lily and the Bird's response to despair in The Sickness unto Death. By suggesting in The Lily and the Bird that we look to nature's creatures to learn an attunement and responsiveness to our situation as physical creatures subject to finite constraints, Kierkegaard's text comes into dialogue with a form of misalignment portrayed in The Sickness unto Death as a refusal of the given, “the finite,” and “the necessary.” One way of seeking alignment in The Lily and the Bird entails learning to hear and to answer within one's given environment, opening up the possibility of embodied joy.